PENGEMBANGAN DAN PERLINDUNGAN KEKAYAAN BUDAYA DAERAH: RESPON PEMERINTAH INDONESIA TERHADAP ADANYA KLAIM OLEH PIHAK LAIN - Patji, Abdul Rahman (Jurnal Masyarakat dan Budaya, 2010)
This article studies about the wealth of Indonesia’s local (ethnical) cultures which were claimed by some foreign countries as well as their private enterprises. The claim has been occurred on until nowadays and possibly to be increased in the future. Facing this phenomenon needs prepare protection effective efforts from all segments of Indonesian societies. The main objective of this article is analyse some efforts of the Government of Indonesia (GoI) for responding to those claims as part of their responsibility for developing and protecting the cultural properties of Indonesian peoples. In this relation some facts shows that the role of Indonesian governments, whether central or regional, are not optimum yet, except the local government of Bali and Yogyakarta. The involvement Indonesian government in the ratification of several international convention on cultural intellectual rights, the development of cultural agreements with many countries as well as the opening of cultural attache offices in the friendly countries are also apparently can not wipe out the claim of foreign countries on Indonesia's local (ethnical) cultures. Keywords: development, protection, claims of foreign countries on Indonesia’s local (ethnical) cultures, role of the GoI (Government of Indonesia)